EFFECT OF PASSIVE INTEGRATED TRANSPONDER (PIT) TAGGING ON HEMATOLOGICAL ALTERATION IN LABEO ROHITA (HAMILTON, 1822) - DAS, ANUSHKA; SAHOO, AMIYA KUMAR; MEENA, DHARMENDRA KUMAR; K. B, SHASHIKALA; BHUYAN, SATYAJIT KUMAR; DAS, BASANTA KUMAR (Journal of the Inland Fisheries Society of India, 2024)
Labeo rohita is one of the commercial important aquaculture species in the South-East Asian countries. Passive Integrated Transponder (PIT)  tagging is a technique used for tracking fish through the implantation of a small Radio Frequency Identification (RFID) microchip, which facilitates long-term identification while ensuring minimal health impact. The study provides the stress physiological responses to intramuscular Passive Integrated Transponders (PIT) tagging in Labeo rohita. A total of 63 fish specimen with average length15cm to 22 cm and weight 125 to 220 g were intramuscularly tagged with PIT over a period of 30 days and the haematological parameters were analysed over a period of 15 min, 30 min, 1 h, 2 h, 4 h, 8 h, 16 h, 2 d, 3 d, 10 d, 15 d, 30 d respectively. The result indicated that the initial hours of tagging, the stress level remain high and gets stabilised after 4 hours of tag insertion. This study emphasizes the necessity of initial stress reduction management during the tagging programme towards mitigating damages to fish health and for welfare.